Are Returns to Private Infrastructure in Developing Countries Consistent with Risks Since the Asian Crisis? - Estache, Antonio (World Bank, Washington, D.C., 2013)
This paper presents a basic assessment of the financial performance of infrastructure service operators in developing countries. It relies on a new database of 120 companies put together to track the evolution of the cost of capital, the cost of equity and the return to equity for electricity, water and sanitation, railways and port operators in 31 developing countries distributed evenly across low-income, low-middle income and upper middle-income countries. The paper shows that between 1998 and 2002, the average cost of capital in developing countries varied from less than 11 percent to over 15 percent across regions and sectors while the cost of equity varied from around 13 percent to over 22 percent. Low-middle-income countries have recovered relatively well from the East Asia crisis, while low-income and upper-middle-income countries have seen their situation deteriorate since the crisis. At the regional level, the main story is that East Asia is recovering quite well from its crisis, and that the financial performance of the operators in Africa and Latin America has deteriorated. Eastern Europe and South Asia are doing relatively better but show a large volatility of returns over time and within sectors. At the sector level, the railways and the energy sectors have seen their performance deteriorate significantly over the period, while the water and port sectors have done relatively better. In all sectors and regions, the average return to equity has been lower than the cost of equity since the Asian crisis.